2018
DOI: 10.1515/sjecr-2016-0083
|View full text |Cite
|
Sign up to set email alerts
|

Older Hypertensive Patients’ Adherence to Healthy Lifestyle Behaviors

Abstract: Non-pharmacological treatment including diet, body weight reduction, smoking cessation and physical activity, is very important part of hypertension treatment. Th e objective of this study was to investigate the adherence to healthy lifestyle behavior in the representative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
10
0
2
Order By: Relevance
“…The level of adherence was classified as high adherent and low adherent (Andjelkovic et al, 2018). The respondent adherent to all the six components was classified as high adherence to lifestyle modifications and low adherence if adherence to any one or more components was missing.…”
Section: Adherence To Salt Intakementioning
confidence: 99%
“…The level of adherence was classified as high adherent and low adherent (Andjelkovic et al, 2018). The respondent adherent to all the six components was classified as high adherence to lifestyle modifications and low adherence if adherence to any one or more components was missing.…”
Section: Adherence To Salt Intakementioning
confidence: 99%
“…Several studies have shown that being advised of an increased genetic risk does not result in any significant change in health behaviors. 151,152 Nor does being diagnosed and treated for hypertension, 153,154 coronary heart disease, 155 type 2 diabetes, 156-159 or chronic disease generally. 155 A study of college athletes found that being advised of increased genetic risk of poor recovery from traumatic brain injury would not affect their playing behavior.…”
Section: Would Knowing Genetic Risk Make a Difference?mentioning
confidence: 99%
“…Ditemukan bahwa pasien usia lanjut memiliki kepatuhan terhadap pola hidup sehat lebih buruk dibandingkan dengan kelompok usia lainnya. 7 Pada usia kurang dari 45 tahun, hipertensi didominasi oleh pria, tetapi pada usia di atas 60 tahun, ditemukan bahwa sebanyak 47% pasien hipertensi adalah wanita dan sebanyak 43% lainnya adalah pria. 8 Penelitian di India mengenai hubungan antara jenis kelamin dan tingkat kepatuhan pasien memperlihatkan bahwa pria memiliki tingkat kepatuhan yang lebih rendah dibanding wanita.…”
Section: Pembahasanunclassified
“…Hal ini sesuai dengan penelitian mengenai kepatuhan pasien hipertensi usia lanjut terhadap pola hidup sehat yang menyatakan bahwa pasien usia lanjut memiliki tingkat kepatuhan yang rendah terhadap pengobatan dan pola hidup sehat. 7 Penelitian ini memiliki keterbatasan yang memungkinkan terjadinya bias, yaitu tingkat keparahan penyakit hipertensi dan juga status pasien baru atau lama tidak diseragamkan, sehingga terdapat kemungkinan hal ini dapat memengaruhi nilai kepatuhan pasien.…”
Section: Jurnal Farmasi Klinik Indonesiaunclassified